Analisis Spasial Temporal Perubahan Tutupan Lahan di Sekitar Waduk Pendidikan Diponegoro menggunakan Data Google Earth - Astuty, Yulia Indri; Wibowo, Adi (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The Diponegoro Education Reservoir is located in Tembalang District, Semarang City, Central Java Province. This reservoir was built for academic purposes and also to control floods around its neighbourhood. Semarang City has a high level of floods vulnerability. Located in the northern part of Java Island which is close to the Java Sea added with limited land availabilty and increased number of human population, make Semarang City is prone to flood. Based on data from the Central Statistics Agency, in 2007 the population in Semarang City was around 1.45 million people, in 2015 it rose to 1.59 million people, and in 2021 it will again increase to 1.65 million people. This increase in population cause various spatial problems that have an impact on flood vulnerability, one of which is the problem of land use. Therefore, a land cover analysis around the Diponegoro Education Reservoir is needed. This study conducted a temporal spatial analysis of land cover for 2007, 2015 and 2022 using Google Earth data. The method used is on screen digitization to obtain 3 classes of land cover classification, namely bodies of water, built-up land and non-built-up land. The hope is that the results of this research can present land cover data around the Diponegoro Education Reservoir in 2007, 2015 and 2022 as input to policy makers regarding spatial planning and disaster for sustainable development.